Comparative evaluation among different materials to replace soft tissue in oral radiology studies (Journal of Applied Oral Science, 2010)
OBJECTIVE: The aim of this study was to establish which materials afford better simulation of soft tissues in Oral Radiology studies. MATERIAL AND METHODS: The sample was composed of four materials in eleven different thicknesses to simulate the soft tissues of the face. The mean values of the relative amounts of radiographic contrast of the materials were determined and compared to a gold standard value, which was obtained from 20 patients who were referred to have periapical radiographs taken of the left mandibular molars. Data were subjected to statistical analysis with Dunnett's test (p